Evaluating strengths and opportunities for a co-created climate change curriculum: Medical student perspectives - Liu, Irene; Rabin, Benjamin; Manivannan, Madhu; Laney, Emaline; Philipsborn, Rebecca (Frontiers in Public Health, 2022)
Introduction Medical trainees are front-line workers in our worsening climate and health crisis. A movement is underway to teach medical students essential climate change and health content. Few evaluations of climate and health curricula exist to support ongoing curricular development, innovation, and improvement. This study explores student perspectives on climate change and health content and delivery post-implementation of a climate change and health curriculum that was co-created by students and faculty and integrated across 16 months of pre-clinical coursework at Emory University School of Medicine. Methods The authors conducted focus groups with the inaugural cohort of students to receive the climate and health education content at the conclusion of their preclinical curriculum. The focus groups elicited student perspectives across four domains: (i) prior perceptions of climate change and health, (ii) current attitudes about climate change and health, (iii) reflections on the existing curriculum, and (iv) opportunities for the curriculum. In this qualitative evaluation, the authors coded focus group transcripts using an inductive content analysis approach. Results Out of 137 eligible students in the cohort, 13 (9.5%) participated in the focus groups. Implementation strategies that students valued included contextualization and integration of climate content within existing topics and student representation through the co-creation process. Students recommended bolstering small group sessions and case-based learning to build relevant history and physical examination skills as well as creating interprofessional and community-based opportunities. Discussion This evaluation offers in-depth student perspectives of our climate and health curriculum. Opportunities exist to synergize climate and health education with broader transformations in medicine toward health promotion and sustainable, climate-ready healthcare. From the input of focus groups, the authors derive a framework for strengthening and extending curricular content.